We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
193
2
avatar+1342 

If f(x) = -2x + 5, determine the value of each of the following:

 

f(-3) = 

 

f(0) = 

 

f(¼) = 

 May 30, 2018
 #1
avatar+18071 
+2

f(x) = -2x +5

f(-3) = -2(-3) + 5

       =   6 + 5

f(-3) = 11                          See how it is done?   Now...you try the other two!   G'Luck!

 May 30, 2018
 #2
avatar+53 
+2

f(-3) = -2(-3) + 5

f(-3) = 6 + 5

f(-3) = 11

 

f(0) = -2(0) + 5

f(0) = 0 + 5

f(0) = 5

 

f(¼) = -2(¼) + 5

f(¼) = -0.5 + 5

f(¼) = 4.5

 May 30, 2018

10 Online Users

avatar
avatar
avatar